STRATEGI PENGEMBANGAN USAHA CAKE BUAH NAGA SEBAGAI IKON OLEH-OLEH ASLI BATAM (Studi Kasus : CV. Aroma Cake Buah Naga, Batam) - Lainatussifa L; Acep Muhib (Departement of Agribusiness Faculty of Science and Technology, 2018)
This study aimed to analyze the business development strategies of dragon fruit cake in C.V. Aroma Dragon Fruit, Batam. The IFE matrix, EFE, SWOT and AHP were employed to formulate strategic priorities for the business. Results of processing matrices AHP showed that priority strategies are an improvement strategy of the management system and the quality of customer service (0,157), a market penetration strategy (0,157), an improvement vision and mission of the company (0.123), and a development of new products in accordance with the development of consumer preferences (0.117 ).